2020
DOI: 10.3389/fpsyg.2020.01767
|View full text |Cite
|
Sign up to set email alerts
|

Molecules of Silence: Effects of Meditation on Gene Expression and Epigenetics

Abstract: Many studies have consistently demonstrated an epigenetic link between environmental stimuli and physiological as well as cognitive responses. Epigenetic mechanisms represent a way to regulate gene activity in real time without modifying the DNA sequence, thus allowing the genome to adapt its functions to changing environmental contexts. Factors such as lifestyle, behavior, and the practice of sitting and moving mindful activities have been shown to be important means of environmental enrichment. Such practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 91 publications
(141 reference statements)
2
17
0
Order By: Relevance
“…These results suggest meditation differentially express several genes related to oxidative stress in agreement with a previous study [33]. The downregulated module also included genes regulating the cell cycle, suggesting that meditation may exert effects on cell cycle regulation through transcriptional regulation, in agreement with previous studies [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest meditation differentially express several genes related to oxidative stress in agreement with a previous study [33]. The downregulated module also included genes regulating the cell cycle, suggesting that meditation may exert effects on cell cycle regulation through transcriptional regulation, in agreement with previous studies [20].…”
Section: Discussionsupporting
confidence: 92%
“…These parameters are typically measured with selfreported surveys before and after meditation interventions, and such an approach may be prone to bias and subjectivity. Several studies on meditative practices have, however, shown changes in gene expression levels demonstrating that these methods may benefit physiology at its most fundamental level [20, 21]. Nevertheless, most of the previous studies are: (a) cross-sectional studies (evaluating only one time-point) [2226], (b) done on highly experienced meditators [22, 23], (c) small sample-sized [2224, 26, 27], (d) tested on handpicked non-specific biomarkers [25, 26], and (e) confounded with different lifestyle and diet [22, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness has a strong impact on brain glutamate and GABA levels observed in the brains of people who practice meditation (e.g., Zen Mediation, Transcendental Meditation, Buddhist Meditation; Fayed et al, 2013;Venditti et al, 2020). A cross-sectional study comparing the brains of meditators from a Zen Buddhist monastery with healthy non-meditators showed differences on glutamate levels in the left thalamus, which may indicate a higher level of efficiency of glutamate metabolism in this area in the case of meditators (Fayed et al, 2013).…”
Section: Natural Boosts For Everyday Functioningmentioning
confidence: 99%
“…Therefore, MBI provides a component corresponding to the environmental abundance. Indeed, MBI changes epigenetic modifications, as well as mental and physical functions as follows [113,114] (Table 2). [115], but there are no reports regarding non-coding RNA at present (Table 2).…”
Section: Potential Mechanism For Diabetes-related Effects Of Mind-body Interventionmentioning
confidence: 99%